Drivers of Green Entrepreneurship Among MSMEs in Jakarta: An Empirical Analysis of Capability, Opportunity, Motivation, Incentives, and Capital Through the Lens of Self-Efficacy - Jesslyn Benedicta Panjaya; Benny Aristo (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study investigates the determinants of green entrepreneurship among Micro, Small, and Medium Enterprises (MSMEs) in Jakarta, an urban economic hub increasingly pressured to adopt environmentally sustainable practices. The research examines the influence of green entrepreneurial skills, green opportunities, entrepreneurial motivation, green incentives, and availability of capital on green entrepreneurship, with green entrepreneurial self-efficacy positioned as a mediating variable. A quantitative survey was conducted with 200 MSME employees who have been engaged in or exposed to green business practices. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all five predictors significantly and positively affect green entrepreneurship. Additionally, green entrepreneurial self-efficacy mediates all relationships, suggesting that cognitive belief systems play a central role in converting resources, opportunities, and motivations into environmentally responsible entrepreneurial behavior. This research contributes to the literature on sustainable entrepreneurship in emerging markets by demonstrating how psychological self-efficacy interacts with structural and motivational factors. The study also provides actionable insights for policymakers, MSME owners, and sustainability-driven institutions in Indonesia.